The impact of legs fat mass and legs lean fat mass on thigh circumference according cardiovascular risk: a population-based study. (11th May 2021) - Chlabicz, M; Paniczko, M; Jamolkowski, J; Sowa, P; Lapinska, M; Szpakowicz, M; Drobek, N; Zalewska, M; Raczkowski, A; Kaminski, K, A
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Medical University of Bialystok, Poland Introduction A low thigh circumference is associated with an increased risk of high blood pressure, diabetes, cardiovascular diseases, and total mortality. Objectives The aim of the study was to investigate the relationship between the thigh circumference and cardiovascular (CV) risk classes, and to assess what type of tissue, adipose tissue or muscle tissue affects the thigh circumference. Methods The longitudinal, population-based, Polish study was conducted in 2017-2020. A total of 931 individuals aged 20-79 were analyzed. Pol-SCORE system was used to assess the 10-year risk of fatal CV based on the following risk factors: age, gender, smoking, systolic blood pressure, and total cholesterol for individuals aged 40-70. Then, CV risk classes were assessed using the 2019 ESC/EAS guidelines. The measurement of thigh circumference were performed directly below the gluteal fold of the thigh. Both thighs were measured and the mean value was calculated as the final thigh circumference. Body composition was assessed using Dual Energy X-ray Absorptiometry (DEXA). Results The mean age was 49.1 ± 15.5 years and 43.2% male. The mean thigh circumference was 58.2 ± 5.9 cm, the mean legs fat mass was 7.7 ± 2.8kg, and the mean legs lean mass was 16.9 ± 4.0kg. Lower thigh circumference was associated with higher CV risk classes in univariate linear regression analysis (β -0.516, p = 0.002), as well adjusted by age and sex (β -0.839, p = 0.008), adjusted by age, sex, BMI (β -0.886, p <0.001), and age, sex, WHR (β -0.988, p <0.001). In linear regression analysis legs adipose tissue and muscle tissue were related to the thigh circumference independently of CV risk classes (Model 1) and Pol-SCORE value (Model 2). However, fatty tissue (Model 1: β 0.746, p < 0.001; Model 2: β 0.749, p < 0.001) affects the thigh circumference more than the muscle tissue (Model 1: β 0.479, p < 0.001; Model 2: β 0.442, p < 0.001) (Fig. 1). Conclusion Smaller thigh circumference was associated with higher CV risk classes. Thigh circumference was more influenced by adipose tissue than by muscle tissue, regardless of the Pol-SCORE or CV risk classes.